2020
DOI: 10.32890/jtom2020.15.2.5
|View full text |Cite
|
Sign up to set email alerts
|

A Framework to Develop Intelligent System for Capturing Product Features Using Open Cv Technique

Abstract: This research aims to propose an innovative framework using ISO14649 standard to detect defects in manufactured shaped objects or geometric surfaces of non-linear products of the CNC machine. The significant importance in order to recognize the potential to improve industry product quality inspection and encourage the waste of timing machines and product rejection. Open Computer Vision (Open CV) offers a smart, non-contact measurement and cost-effective technique to fulfil the requirements. The framework depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Pathan et al, (2021) research further established the link between leadership and effective employee performance. Saif et al, (2020) also looked at this issue and discovered that leadership has a big impact on worker performance. In their study, discovered a substantial relationship between motivation and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Pathan et al, (2021) research further established the link between leadership and effective employee performance. Saif et al, (2020) also looked at this issue and discovered that leadership has a big impact on worker performance. In their study, discovered a substantial relationship between motivation and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that blend B10 of coconut oil was one of the finest alternative fuel replacements for diesel fuel running in a four-stroke water-cooled diesel engine. The authors' findings suggest that the use of biodiesel produced from different blends of coconut oil and cotton seed oil can be a promising alternative source of energy for reducing greenhouse gas emissions and mitigating environmental impacts... Saif, Y. et al, 2020). They analyzed 2750 publications from their data storage collection base at Web of Science Core from 2000 to 2020 using ArcGIS 10.2, VOS viewer.…”
mentioning
confidence: 99%